(untitled) (Research, Society and Development, 2020)
Objective: To assess the level of knowledge of parents, teachers and dental surgeons in the city of Caicó-RN about the use of fluoride toothpaste in children. Material and Methods: The study is of a descriptive nature, cross-sectional with quantitative description with parents or guardians who took children at the UERN children’s clinic, professors of the Dentistry course at the same university and dental surgeons from the public network of Caicó-RN. Questionnaires were used with questions related to the use of fluoride toothpaste for children under 7 years old. The data were analyzed using statistics that included frequency distribution and association tests. Results: More than 40% of the sample does not know the correct time to start using fluoride dentifrices, more than 50% of the sample indicates a greater quantity than that recommended for children under 7 years of age, the majority of teachers and dentists they know the correct prescription to be indicated. Conclusion: Parents and / or guardians do not have knowledge about the current prescription of fluoridated toothpastes for their children.